Beger procedure in a 20-year-old female with solid pseudopapillary tumour of the pancreas - Szwedziak, Krzysztof; Durczyński, Adam; Danilewicz, Marian; Strzelczyk, Janusz (Contemporary Oncology/Współczesna Onkologia, 2014)
Solid pseudopapillary tumour is a rare indolent neoplasm of the pancreas (< 2% of exocrine pancreatic tumours), which predominantly affects young women at reproductive age, without significant clinical symptoms. We report a case of a 20-year-old Caucasian female who presented with upper abdominal pain of one-year duration. Ultrasound scans of the abdomen demonstrated enlarged pancreatic head and body containing a poorly separated mass (52 × 41 × 36 mm) with a multi-cystic component 20–24 mm in diameter. Laboratory tests including, tumour markers levels, were normal. She underwent complete resection of the tumour using a Beger procedure. By immunohistochemistry, the case stained strongly for CD10 and CD56 and was negative for cytokeratin-7 (CK-7), synaptophysin and chromogranin A. The proliferation index (Ki-67) was < 1%. The patient is being followed-up and remains healthy. Conclusions : Solid pseudopapillary tumour is a tumour with low potential of malignancy and with generally favourable prognosis; surgical resection is usually curative.